#Unrequited potentiality of socially and politically committed theatre. Issue 207 (1st June 2022) - Zupan, Metod
In 2018 Zala Dobovšek and Jaka Smerkolj Simoneti examined how LGBTQ+ characters are represented on the stages of Slovene public theatres. In their overview they concluded that rather than being the centre of the narrative, these representations are most often supporting roles. In that sense the play #scars #chemsex (#brazgotine #kemseks) is not only a breath but a strong nudge of fresh air.